Professional Mosque Management Through Application-Based Mosque Management - Supardin, Lalu; Adi Prabowo, Adia; Leli Indratno, Diana (EMPOWERING HUMANITY, 2023)
Considering how important the existence of the mosque is for the Imam community and how muchresponsibility the mosque manager carries, it certainly requires good mosque management. Managementitself has four main pillars that are the foundation in the field of management science, namely: planning,organizing, movement/direction (actuating), and supervision (controlling). The function of managementitself is to plan, organize, coordinate and control resources so that goals can be achieved effectively andefficiently.Application-based mosque management aims to provide more knowledge to mosque administratorsin managing mosques in a professional, accountable and transparent manner. In addition, applicationbased mosque management will educate mosque administrators to use technological and informationadvances in managing, recording and reporting all forms of important information in a professional,accountable and transparent manner. Therefore, application-based mosque management is essentiallytraining and developing the ability of human resources (HR) in managing mosques in accordance withthe progress and demands of the times. This is where the role of application-based mosque managementis needed in managing the mosque professionally, accountably and transparently.